Process for catalytic conversion of plastic waste to olefins.
By controlling the depolymerization reaction of the temperature-controlled depolymerization reaction containing high-content polyester waste, the problem of low allylic gas production in the prior art is solved, and the efficient production of light gas allylic is achieved, reducing energy consumption and emissions.
Patent Information
- Application Number
- JP2024552423
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-30
- Filing Date
- 2023-03-30
- Publication Date
- 2025-04-15
Smart Images

Figure 2025510551000001 
Figure 2025510551000002 
Figure 2025510551000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to the depolymerization of waste polymers. More specifically, the present disclosure relates to a process for directly converting waste polymers into olefins via a depolymerization reaction. [Background technology]
[0002] Plastics include a variety of synthetic and semi-synthetic materials that use polymers as their primary components. Their plasticity allows them to be molded, extruded, or pressed into solid objects of various shapes. This adaptability, combined with a variety of other properties such as light weight, durability, and low production costs, has led to their widespread use. The production of plastics has increased dramatically over the past decades. At the same time, the increase in the amount of plastics poses environmental problems, since most plastics are resistant to natural degradation processes. As such, the material can persist for centuries or more, filling up landfills and even appearing in the food chain as microplastics.
[0003] Therefore, efforts are being made to improve the recycling of polymer waste. Current recycling procedures mainly rely on mechanical and chemical recycling. In mechanical recycling, plastics are mechanically transformed without changing their chemical structure, making them available for the production of new materials. The general mechanical recycling process includes collecting the polymer waste, sorting the polymer waste into different types of plastics and colors, baling the plastic waste by pressing or crushing, washing and drying the polymer waste, and reprocessing the polymer waste into pellets by agglomerating, extruding and cooling the plastics to obtain recycled raw materials that can then be molded into new articles.
[0004] During chemical recycling, plastics are reprocessed and their structure and chemical properties are modified so that they can be used as raw materials in various industries or as basic inputs or feedstocks for the manufacture of new polymer products. Chemical recycling generally involves the recovery of plastic waste and then heating it to break down the polymers to obtain smaller organic molecules that are then recycled in the petrochemical industry.
[0005] Typically, the main output from a pyrolysis process is a liquid stream, also called pyrolysis oil, which can either be refined and used as a fuel or subjected to a further steam cracking process to produce a gaseous fraction composed of C2-C4 olefins.
[0006] One problem associated with this process is that the total yield of olefins, such as ethylene and propylene, is only about 35% based on the plastic feedstock.
[0007] In light of the above, there remains a need for more efficient processes for converting plastic waste into C2-C4 olefin products. Summary of the Invention
[0008] In one aspect, the present disclosure provides a process for the conversion of plastic waste to olefins, comprising:
[0009] (i) depolymerizing a plastic scrap feedstock containing more than 80% by weight polyolefins based on a polymer fraction of the plastic scrap feedstock in the presence of a catalyst at a temperature ranging from 400 to 700°C, the polymer fraction of the scrap containing non-polyolefin organic components in an amount of less than 7.0% by weight, preferably less than 6.0% by weight, more preferably less than 5.0% by weight, based on the total weight of the dry weight polymer fraction of the scrap feedstock;
[0010] (ii) recovering the gaseous fraction generated during pyrolysis; and
[0011] (iii) separating the recovered gaseous fraction to obtain a gaseous depolymerization product and a liquid depolymerization product, wherein the amount of the gaseous depolymerization product is greater than 60 wt.%, based on the total polyolefin content, but in the gaseous depolymerization product, the amount of C2-C4 olefins is greater than or equal to 65 wt.%, based on the total amount of hydrocarbons. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Preferably, the plastic waste feedstock is characterized in that (a) it has a polyolefin content, in particular a total polypropylene (PP) and polyethylene (PE) content, of more than 85 wt.-%, more preferably more than 90 wt.-%, in particular more than 95 wt.-%, based on the total weight of the polymer waste feedstock.
[0013] Preferably, the upper limit for the polyolefin content is 99% by weight, more preferably 98% by weight, especially 97% by weight, based on the total amount of plastic waste feedstock.
[0014] It is also a preferred embodiment that the weight ratio PE / PP in the polymer waste raw material is 2 or more, preferably 3.5 or more, more preferably 5 or more, especially 6 or more. Furthermore, the total ash content of the plastic waste feedstock is preferably less than 35% by weight, more preferably less than 30% by weight, determined as the residue after heating the polymer waste feedstock at 800°C in air for 120 hours.
[0015] Preferably, the plastic waste feedstock is also characterized in that (i) it has a bulk density of 70-500 g / L, preferably 100-450 g / L, if the polymer waste feedstock is present in shredded form, or 300-700 g / L, if the polymer waste feedstock is in pellet form, the bulk density being determined in accordance with DIN 53466, respectively. It has been found that the above bulk density values are of great help in realizing a continuous flowless depolymerization process and in preventing clogging of the feed lines and fouling of the reactor. Furthermore, it also helps in reducing the amount of residues and intensifying the depolymerization reaction, leading to a higher yield of the desired product. Preferably, the polymer waste is obtained from shredded pipes with a particle size of less than 50 mm, preferably less than 30 mm, more preferably less than 20 mm, most preferably less than 15 mm.
[0016] In a preferred embodiment, the plastic waste feedstock is additionally characterized by: (i) a total volatiles (TV) content of less than 4%, preferably less than 3%, measured as the weight loss of a 10 g sample after 2 hours at 100°C and 200 mbar.
[0017] In addition to the polyolefin components described above, the plastic scrap feedstock used in the process of the present disclosure can include essentially any polymeric material, especially polymeric materials formed from synthetic polymers. Non-limiting examples include polyolefins other than PE and PP, such as polybutene-1 and ethylene-propylene elastomers, polystyrene, polyethylene terephthalate (PET), polyvinyl chloride (PVC), polyamides, polycarbonates, polyurethanes, polyesters, natural and synthetic rubber, tires, filled polymers, composites and plastic alloys, plastics dissolved in solvents, and the like.
[0018] However, in accordance with the present disclosure, which is directed to maximizing the production of light gas olefins, the plastic feedstock preferably consists primarily of polyolefins, and non-polyolefin polymeric materials may be present only in the amounts described above.
[0019] As mentioned above, the plastic waste feedstock may consist of one type of polyolefin waste or may be a mixture of two or more different polymer waste materials. Particularly preferred is an embodiment in which the polyolefin waste material consists entirely of polyethylene (PE).
[0020] A particularly preferred polyolefin waste material is crosslinked polyethylene. Preferably, the crosslinked polyethylene is selected from the group consisting of peroxide crosslinked polyethylene, silane crosslinked polyethylene, radiation crosslinked polyethylene, radical crosslinked polyethylene, azo crosslinked polyethylene, ultraviolet-initiated radical crosslinked polyethylene, and mixtures thereof.
[0021] The plastic waste feedstock may be provided in a variety of different forms. In smaller scale operations, the polymer waste feedstock may be in the form of a powder. In larger scale operations, the polymer waste feedstock is preferably in the form of pellets, such as having a particle size of 1-20 mm, preferably 2-10 mm, more preferably 2-8 mm, or may be in the form of chopped flakes and / or film pieces, preferably having a particle size of 1-20 mm. In the context of this disclosure, having a particle size within a specified range means that 90% by weight of the particles have a particle size that is within the specified range. Particle size may be measured by sieving or using a Beckman Coulters LS13320 laser diffraction particle size analyzer.
[0022] The plastic waste materials disclosed above are mainly composed of plastic materials and are usually named after the type of polymer that forms the main component of the polymer waste material. Preferably, the plastic waste materials used as raw materials in the process of the present disclosure contain more than 50% by weight, preferably more than 60% by weight, more preferably more than 70% by weight of polymer material of the total weight of the plastic waste material. Other components in the polymer waste raw material may be additives such as fillers, reinforcing agents, processing aids, plasticizers, pigments, light stabilizers, lubricants, impact modifiers, antistatic agents, inks, antioxidants, etc.
[0023] In certain embodiments, the polymer waste used in the process of the present disclosure preferably comprises polyolefins such as high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ethylene-propylene-diene monomer (EPDM), polypropylene (PP), etc. Certain polymer waste comprises a mixture of polyolefins with less than 3% polystyrene (PS), preferably less than 2% by weight.
[0024] Other non-polyolefin polymer scraps such as polyamides, polyvinyl chloride, polyvinylidene chloride, polyethylene terephthalate, polyurethane (PU), acrylonitrile butadiene styrene (ABS), nylon, and fluorinated polymers are preferably not present in the polymer scrap, and if present, they are preferably present in an amount of less than 3%, especially less than 2%, of the total weight of the polymer scrap feedstock on a dry weight basis.
[0025] Preferably, the polymer waste is essentially free of thermosetting polymers, where substantially free means that the thermosetting polymer content is less than 3% by weight, and even more preferably less than 2% by weight, of the polymer waste feedstock.
[0026] The plastic waste material used in the process of the present disclosure is preferably selected from the group consisting of single plastic waste, mixed plastic waste, and rubber waste. Single plastic waste, off-spec single virgin plastic, mixed plastic waste, rubber waste, or a mixture thereof is preferred. In particular, off-spec single virgin plastic, mixed plastic waste, or a mixture thereof is particularly preferred.
[0027] The plastic waste may also contain limited amounts of non-pyrolyzable inorganic components as foreign matter, such as water, glass, stones, metals, etc. By "limited amounts" it is preferably meant an amount less than 35% by weight, more preferably less than 30% by weight, of the total weight of the dry plastic waste feedstock.
[0028] The plastic waste may optionally be extruded prior to use as a feedstock in the disclosed process. In a preferred embodiment, the plastic waste is pelletized and the pellets are used as a feedstock in the disclosed process. In another preferred embodiment, the plastic waste is used in a molten state, for example at a temperature of 200°C to 300°C.
[0029] Particularly preferred types of plastic waste used as a feedstock in the process of the present disclosure are characterized by the following features:
[0030] i) the polyolefin content in the polymer waste, in particular the polypropylene (PP) and / or polyethylene (PE) content, is greater than 80% by weight, preferably greater than 85% by weight, more preferably greater than 90% by weight, in particular greater than 95% by weight, based on the total weight of the polymer waste raw material;
[0031] ii) the polymer waste is shredded, optionally compressed, polymer waste and has a bulk density of 70-500 g / L, preferably 100-450 g / L, or the polymer waste is in pellet form and has a bulk density of 300-700 g / L, the bulk density being measured according to DIN 53466;
[0032] iii) a total content of volatiles (TV), measured as the weight loss of a 10 g sample after 2 hours at 100° C. and 200 mbar pressure, of less than 5%, preferably less than 3%, more preferably less than 2%, in particular less than 1%;
[0033] iv) the amount of polar polymeric impurities in the polymer waste is less than 3 wt. %, more preferably less than 2 wt. %, based on the total weight of the polymer waste;
[0034] v) the amount of cellulose, wood and / or paper in the plastic waste is less than 5% by weight, more preferably less than 3%, based on the total weight of the polymer waste;
[0035] vi) a total chlorine content of less than 1.0 wt.%, preferably less than 0.5 wt.%, more preferably less than 0.1 wt.%, based on the total weight of the polymer waste;
[0036] vii) The total ash content of the polymer waste feedstock is less than 10 wt%, more preferably less than 5 wt%, and most preferably less than 3 wt%, measured as the residue after heating the polymer waste in air at 800° C. for 120 hours. In another preferred embodiment, the ash content is between 0.01-2 wt%, preferably between 0.02-1.5 wt%, more preferably between 0.05-1.0 wt%.
[0037] In a preferred embodiment of the present disclosure, the plastic waste used as a raw material in the process of the present disclosure is defined by upper limits of trace components, constituents or impurities expressed in weight percent. The lower limits of the amount of these components, constituents or impurities in the preferred polymer waste are preferably below the detection limit, or the lower limit is 0.001% by weight or 0.01% by weight or 0.1% by weight, respectively.
[0038] A variety of techniques are known for separating materials in polymer waste streams. Moving beds, drums and screens, and air separators are used to fractionate materials according to size, weight, and density. Advanced sorting of plastic waste by spectroscopy (MIR, NIR [near infrared]), X-ray, or fluorescence spectroscopy provides high quality plastic waste streams with high polyolefin content.
[0039] Automated sorting technologies for waste plastics include dry sorting technologies, electrostatic sorting technologies, mechanical sorting methods (including centrifugal force, specific gravity, elasticity, particle shape, selective crushing, and mechanical properties), as well as wet sorting technologies (e.g., sinking and flotation sorting methods), and chemical sorting methods.
[0040] Suitable raw materials for use in the process of the present disclosure can be obtained by applying any of the known sorting techniques, for example as summarized in B. Ruj et al: Sorting of plastic waste for effective recycling, Int. J. Appl. Sci. Eng. Res 4, 2015, 564-571.
[0041] Depolymerization
[0042] According to the present disclosure, a process for depolymerization of plastic waste comprises pyrolysis of the plastic waste at a temperature in the range of 400-700°C, optionally in the presence of a catalyst.
[0043] The gaseous effluent from the pyrolysis reactor is then (a) recovered and (b) separated into a gaseous depolymerization product and a liquid depolymerization product.
[0044] Preferably, the depolymerization reaction is carried out at a temperature in the range of 420 to 600°C, more preferably 420 to 550°C.
[0045] The recovered gaseous fraction may be separated by condensation into a liquid depolymerization product and a gaseous depolymerization product, which may then be further processed.
[0046] The process of the present disclosure may produce little or no char. Thus, in a preferred embodiment, the residue of the depolymerization process of the present disclosure has a char content of less than 5 wt.%, preferably less than 2 wt.%, based on the total weight of the product.
[0047] The resulting liquid depolymerization product may be further separated. Thus, the process of the present disclosure may further comprise a step of distilling the liquid depolymerization product.
[0048] The process of the present disclosure results in a depolymerized product with a high gas content. In a preferred embodiment, the gas content in the depolymerized product is preferably greater than 70 wt.%, more preferably greater than 75 wt.%, especially greater than 80 wt.%, based on the weight of the polymer fraction of the plastic waste feedstock.
[0049] Moreover, the gaseous fraction of the depolymerization product is further characterized by a high content of monomeric olefinic C2-C4 compounds which are particularly useful for further processing, e.g., for the production of polymers. In particular, the amount of olefinic C2-C4 compounds is 70% or more, preferably 72% or more, in particular 75% or more, based on the total amount of hydrocarbons in the gaseous fraction.
[0050] Furthermore, the amount of C2-C4 hydrocarbons in the gaseous fraction of the depolymerization product is higher than 80%, preferably higher than 85%, in particular higher than 90%, based on the total amount of hydrocarbons in said gaseous fraction. Due to the high amount of such compounds produced during depolymerization, the gaseous depolymerization product may be used directly as a feedstock in a cracking process and subsequent polymerization. The gaseous product, including light olefins and light alkanes, may be transferred to a downstream cracker, for example by passing through an oven, to produce a polymerization grade monomer stream.
[0051] Other by-products such as ethane, propane, and butane can be cracked in an oven, thus saving valuable energy and reducing CO2 emissions by eliminating the normally required step of processing the product obtained after depolymerization to obtain the desired monomers.
[0052] The depolymerization process according to the present disclosure can be carried out in a reactor including (a) a feeding device for introducing polymer waste and a catalyst into the reactor, (b) a pyrolysis device equipped with a heating unit, a gas discharge unit and a solid discharge unit, and (c) a condensation device.
[0053] Preferably, gas discharge units are distributed throughout the pyrolysis device and are provided with an outlet for discharging the gaseous fraction of the depolymerization and an inlet for introducing a wash gas into the pyrolysis device.
[0054] In a preferred embodiment, the reactor may comprise two or more pyrolysis units.
[0055] The polymer waste feedstock and catalyst are introduced into the pyrolysis unit through at least one feeder and then heated to achieve depolymerization. The gaseous fraction produced during depolymerization is discharged through the outlet of the gas discharge unit and conveyed to a condensation unit for further processing. The solid residue of the depolymerization, if any, is discharged through a solid discharge unit. A washing gas for washing the gas discharge unit and the pyrolysis unit may be introduced through the inlet of the gas discharge unit.
[0056] In a preferred embodiment, the gas discharge unit is equipped with a filter membrane to ensure that the gaseous fraction is free of solids after being discharged from the pyrolysis device. The gas discharge unit is preferably made of metal or ceramic particle or fiber material.
[0057] The pyrolyzer is preferably further equipped with a screw for uniformly mixing the polymer waste in the pyrolyzer throughout the depolymerization. The residence time of the solids in the pyrolyzer could be clearly defined by adjusting the rotation speed of the screw. Preferred are embodiments of the present disclosure in which the residence time of the waste is 60 minutes or less, preferably 45 minutes or less. The pyrolyzer is preferably operated at a temperature of 400-550°C.
[0058] The gaseous fraction discharged from the depolymerization is conveyed to a condenser to obtain a liquid depolymerized product and a gaseous depolymerized product. In a preferred embodiment, the condenser includes a plurality of condensers preferably operated at different temperatures. The temperature of the condenser may be set according to the boiling point of the condensate.
[0059] As mentioned above, a catalyst is used in the depolymerization stage of the process of the present disclosure.
[0060] In principle, any catalyst capable of promoting the depolymerization reaction can be used, but it is preferred that the catalyst is not a fluid catalytic cracking catalyst.
[0061] In a preferred embodiment of the present disclosure, the catalyst is selected from catalysts comprising as active components an acidic compound deposited on a particulate non-porous support with the aid of a coating agent.
[0062] In fact, it has been surprisingly found that the catalyst of the present disclosure greatly aids in producing high purity depolymerization products with high gaseous fraction content and low char production. Moreover, the catalyst of the present disclosure has been found to be easily separable from any solid residues of the depolymerization process, thus allowing for multiple uses.
[0063] Preferably, the catalyst of the present disclosure is in particulate form. Particulate non-porous supports selected from the group consisting of sand, glass beads, and metal particles are preferred. Particulate non-porous supports can have any shape, such as spherical, cylindrical, or any non-homogeneous shape. The supports used in the catalyst of the present invention are not only particulate, but also non-porous. Non-porous in the sense of the present disclosure is understood as being impermeable to gases, such as air, or liquids, such as water. In order to design the catalyst of the present disclosure in particular to be mixed with polymer waste undergoing depolymerization, the supports have an average particle size D50 of 0.2-20 mm, preferably 0.5-10 mm, more preferably 1-8, and most preferably 1-6 mm, determined according to sieve analysis in accordance with ISO3310-1 / ASTM E11. An example of a sieving device that can be used is the Retsch test sieve device equipped with a woven wire mesh sieve (Φ125 mm-20 μm).
[0064] Sand is a preferred type of non-porous particulate support and preferably has the following particle size distribution: [Table 1]
[0065] The acidic compounds of the catalyst of the present disclosure are preferably selected from the group consisting of Al / Si mixed oxides, Al2O3, aluminosilicates, silica and zeolites. The Al / Si mixed oxides particularly preferred in the present disclosure refer to materials comprising a mixture of Al2O3 and SiO2 with a neutral structure.
[0066] Particularly preferred zeolites referred to in this disclosure have the general structure M n +x / n[AlO2]-x(SiO2) y ]+zH2O, where n is the charge of the cation M, typically an alkali metal or alkaline earth metal or a hydrogen ion, preferably H + , Na + , Ca2 + , K + and Mg2 + It is to be understood that zeolites are crystalline microporous aluminosilicates built up from corner-sharing SiO4- and AlO4-tetrahedra with z being an ion selected from the group consisting of z, z defining the number of water molecules incorporated in the crystal structure. Zeolites differ from Al / Si mixed oxides by their well-defined pore structure and ionic properties. In a particularly preferred embodiment, the zeolite used as acidic compound is selected from the group consisting of zeolite Y, zeolite beta, zeolite A, zeolite X, zeolite L and mixtures thereof, in particular zeolite Y and zeolite beta. The listed zeolites are well known and commercially available. Zeolites in which the metal ion M is replaced by hydrogen are particularly preferred. Other specific examples of suitable zeolite-type components for use in the present disclosure include, but are not limited to, ZSM-5, ZSM-11, ZSM-22, ZSM-23, ZSM-35, ZSM-48, ZSM-50, TS-1, TS-2, SSZ-46, MCM-22, MCM-49, FU-9, PSH-3, ITQ-1, EU-1, NU-10, silicalite-1, silicalite-2, boralite-C, boralite-D, BCA, and mixtures thereof.
[0067] In a particularly preferred embodiment, the acidic compound is an Al / Si mixed oxide. The composition of the Al / Si mixed oxide used as the support can be adjusted as necessary. However, particularly favorable depolymerization results are obtained when the acidic compound contains certain amounts of Al2O3 and SiO2. Thus, in a preferred embodiment, the acidic compound contains Al2O3 in an amount of 20-99 wt.%, preferably 30-80 wt.%, in particular 40-70 wt.%, based on the total weight of the acidic compound. Furthermore, the acidic compound contains SiO2 in an amount of 1-80 wt.%, preferably 20-70 wt.%, in particular 30-60 wt.%, based on the total weight of the acidic compound.
[0068] Preferably, the acidic compound contains an excess of Al2O3 relative to SiO2. Further preferred are embodiments in which the weight ratio of Al2O3 to SiO2 in the acidic compound is from 99:1 to 30:70, preferably from 9:1 to 3:2, in particular from 4:1 to 3:2.
[0069] Measurement of the SiO2 and Al2O3 content of acidic compounds can be performed by inductively coupled plasma atomic emission spectroscopy (ICP-AES).
[0070] The coating agent used in the catalyst of the present disclosure is preferably selected from the group consisting of oil, inorganic hydrogel, or a combination thereof. As an inorganic hydrogel, silica hydrogel is preferred. As for the oil used as the coating agent, a white mineral oil, preferably based on isoparaffin, and free of aromatics, is preferred. In a preferred embodiment, the oil used has a kinematic viscosity at 20°C of 140-180 mm 2 / s, preferably 150-170 mm 2 / s and / or a kinematic viscosity at 40°C of 40 to 80 mm 2 / s, preferably 50-70 mm 2 / s and / or a kinematic viscosity at 100°C of 5 to 15 mm 2 / s, preferably 7 to 10 mm 2 / s. Kinematic viscosity can be determined according to ISO 3104.
[0071] The preferred amount of the coating agent is in the range of 1-300%, preferably 2-150% by weight, more preferably 5-100% by weight, and most preferably 10-80% by weight, based on the amount of the acidic compound. In the case of a hydrogel, the amount used is expressed as a dry weight.
[0072] In a further preferred embodiment, the active compound is included in the catalyst of the present disclosure in an amount of 0.5-6 wt. %, preferably 2-4 wt. %, based on the total weight of the catalyst.
[0073] The catalyst of the present disclosure is preferably obtained by mixing a particulate non-porous carrier with a coating agent, and then adding an acidic compound in powder form to the resulting mixture. The mixture may be optionally heat-treated to obtain the catalyst. The heat treatment may be carried out, for example, at a temperature of 100 to 600°C. In a preferred embodiment, the particulate non-porous carrier is subjected to a drying process before being mixed with the coating agent.
[0074] In a preferred embodiment, the catalyst is obtained by a process comprising the steps of: (a) mixing a particulate non-porous support with a coating agent; and (b) adding an acidic compound in powder form to the mixture of step (a).
[0075] In a particularly preferred embodiment, the catalyst is characterized as follows: (a) sand as a particulate non-porous support, (b) Al / Si mixed oxide or zeolite as the acidic compound, and (c) mineral oil or silica hydrogel as the coating agent.
[0076] depolymerization products
[0077] The gaseous fraction produced during pyrolysis is separated, for example by condensation, into liquid and gaseous depolymerization products.
[0078] The process of the present disclosure results in depolymerized products with surprisingly high selectivity for gaseous fractions.
[0079] liquid depolymerization products
[0080] The resulting liquid depolymerized product exhibits a surprisingly low content of aromatics, and in particular a surprisingly low content of polycyclic aromatics and asphaltanes. Thus, the liquid depolymerized product obtained by the process of the present disclosure is characterized by a low content of aromatics and olefinic components and a high purity.
[0081] Preferably, the content of aromatics in the obtained liquid depolymerization product is less than 10 mol %, preferably less than 5 mol %, in particular equal to or less than 3 mol %, the content of aromatic components being measured as the content in mol % of aromatic protons determined by H-NMR spectroscopy.
[0082] In addition, the liquid depolymerized product obtained by the depolymerization process of the present disclosure is characterized by a low content of olefinic compounds, the content of olefinic compounds in the liquid depolymerized product is preferably less than 7 mol%, more preferably less than 5 mol%, and even more preferably less than 3 mol%, based on the total number of hydrocarbon protons, and the content of olefinic compounds is determined based on the content of olefinic protons as determined by 1H-NMR spectroscopy.
[0083] Another measure of the content of double bonds in a given sample is the Bromine number (BrNo.), which indicates the degree of unsaturation. In a preferred embodiment, the liquid depolymerized product obtained by the process of the present disclosure has a Bromine number, expressed as grams of bromine per 100 grams of sample, of less than 150, preferably 10-100, more preferably 15-80, even more preferably 20-70, and especially 25-100, measured according to ASTM D1159-01.
[0084] The liquid depolymerization product obtained by the process of the present disclosure preferably has a boiling point range of 30 to 650° C., more preferably 50 to 250° C. By separation techniques such as distillation, the depolymerization product can be separated into hydrocarbon fractions of different boiling point ranges, for example, a light naphtha fraction containing mainly C5 and C6 hydrocarbons with a boiling point range of 30° C. to 130° C., a C6 to C8 hydrocarbon fraction with a boiling point range of 130° C. to 220° C., and a light naphtha fraction containing mainly C5 and C6 hydrocarbons with a boiling point range of 130° C. to 220° C. 12 Heavy naphtha fraction containing mainly hydrocarbons, C9-C with a boiling range of 220°C to 270°C 17 It may be separated into a kerosene fraction containing primarily hydrocarbons, or other higher boiling fractions such as diesel fuel, fuel oil, or hydrowax.
[0085] Even more surprisingly, it has been found that the liquid depolymerization product contains little or no solid residue, and in a preferred embodiment, the liquid depolymerization product upon evaporation has a residue content of 5 ppm(w) or less, as measured according to ASTM D381.
[0086] Gaseous depolymerization products
[0087] The resulting gaseous depolymerization product exhibits a surprisingly low content of low molecular weight hydrocarbons such as methane or ethane. Rather, it has been surprisingly found that the gaseous depolymerization product contains unusually high amounts of higher olefins such as ethylene, propylene, and butenes, which are typically desired for polyolefin production.
[0088] As described above, the amount of olefinic C2-C4 compounds is preferably 70% or more, preferably 72% or more, particularly 75% or more, based on the total amount of hydrocarbons in the gaseous depolymerization product. Therefore, the gaseous depolymerization product obtained by the process of the present disclosure has a high content of any one of ethylene, propylene, and butene, and also has a high content of saturated low molecular weight hydrocarbons, particularly those represented by the general formula C n H 2n+2 (wherein n is a real number in the range of 1 to 4) is characterized by a low content of hydrocarbons.
[0089] Thus, in a preferred embodiment, the gaseous depolymerization product of the disclosed process is characterized by a methane content of at most 7 wt.-%, preferably at most 5 wt.-%, more preferably at most 3 wt.-%, most preferably at most 2 wt.-%, in particular at most 0.5-1.5 wt.-%, based on the total weight of the gaseous depolymerization product after step (e) of the disclosed process.
[0090] Due to its very high olefin content, the gaseous fraction can be used directly as a feedstock for further processing in downstream crackers, e.g., feed gas compressors to obtain purified monomer streams, which can then be used for the subsequent production of polymers, thus avoiding the energy-intensive stream cracking ovens normally required and at the same time reducing CO2 emissions.
[0091] The gaseous depolymerization products may contain small amounts of HCl, HCN, H2S, H2O, NH3, COS, etc., which can be removed in a purification step before being introduced into the downstream segments of the steam cracker.
[0092] The present disclosure will now be explained in more detail with reference to the following figures and examples. EXAMPLES
[0093] The following analytical methods were employed:
[0094] 1) GC MS was used for liquid and gas analysis.
[0095] 2) After decoking the reactor residue at 800°C, the char residue was determined by mass balance.
[0096] 3) The liquid content was characterized using simulated distillation (SimDist) analysis according to ASTM D 7213:2012. The final boiling point (FBP), boiling temperature at 50%, and initial boiling point (IBP) are obtained from SimDist.
[0097] 4) The total content of unsaturated components in the liquid condensate was characterized by bromine number measurement using an 848 Titrino Plus (Metrohm AG, Herisau, Switzerland) equipped with a double PT-wire electrode with integrated PT1000 temperature sensor and a 10 mL burette, according to ASTM D1159-01 described in Metrohm Application Bulletin 177 / 5e (December 2018). The bromine number (BrNo.) indicates the amount of bromine in grams absorbed by 100 g of sample.
[0098] 5) 1H-NMR analysis was performed by dissolving a sample of the liquid condensate in CDCl3 and characterizing the sample using proton NMR spectroscopy. Aromatic, olefinic, and aliphatic protons were assigned according to the chemical shifts summarized in Table 1.
[0099] [Table 2]
[0100] The olefinic proton types listed are assumed to correspond to the following structures: [ka]
[0101] The amounts of aromatic, olefinic and aliphatic protons may be determined based on the assigned peak integrals according to the following formula:
[0102] Mole% of aromatic protons = [(I1+I2) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%
[0103] Mole% of olefin proton type 1=[(I4+I7) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%
[0104] Mole% of olefin proton type 2=[(I3+I5) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%
[0105] Mole% of olefin proton type 3=[(I6) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%
[0106] Mole% of olefin proton type 4=[(I8) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%
[0107] Molar % of paraffin protons = [(I9) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%
[0108] 6) The moisture content of the catalysts was measured at 180 °C on 0.5–1 g samples using a Sartorius MA45 (Sartorius AG, Goettingen, Germany).
[0109] 7) To determine the pH value of the hydrodepolymerization product, a liquid sample of the hydrodepolymerization product was extracted with water at a water:sample volume ratio of 1:5, and the pH value of the aqueous solution was measured.
[0110] 8) Particle size distribution of particulate non-porous supports and catalysts was determined by Coulter Counter analysis according to ASTM D4438.
[0111] 9) The characteristics of the organic waste materials used were determined as follows:
[0112] Because the composition of organic waste materials can vary, 20-100 g samples of polymer waste were ground and analyzed. Alternatively, pelletized samples of polymer waste were analyzed. Use the following method:
[0113] i) Total Volatile (TV) was determined as the weight loss of a 10 g sample after 2 hours at 100° C., 200 mbar.
[0114] ii) The water content was determined by Karl Fischer titration using a Metrohm 915 KF Ti-Touch instrument equipped with a PT100 indicator electrode for KF volumetric titration according to Metrohm Application Bulletin 77 / 3e in accordance with ASTM E203.
[0115] iii) IR spectroscopy was used to qualitatively identify different polymers (PP, PE, PS, PA, PET, PU, polyester) and additives such as CaCO3.
[0116] iv) Standard elemental analysis was used to determine the weight % of H, C, N (DIN51732:2014-07) and S (tube furnace, ELTRA GmbH, Haan, Germany, DIN51724-3:2012-07).
[0117] v) 1H-NMR was used to determine the composition of polymers soluble in a solvent suitable for recording 1H-NMR spectra, i.e. PE / PP balance (including copolymers), PET, PS.
[0118] vi) The ash content analysis of plastics was determined at 800 °C according to DIN EN ISO 3451-1 (2019-05).
[0119] vii) The bulk density of the polymer waste was determined according to DIN 53466.
[0120] viii) Corrosivity was measured as the pH value of the aqueous solution after a contact time of 3 hours (5 g of sample in 50 mL of distilled water).
[0121] ix) Quantitative elemental measurements (total chlorine content, Si or metal content) were performed using inductively coupled plasma atomic emission spectroscopy (ICP-AES).
[0122] x) Determine the ash content of liquid feedstocks such as pyrolysis oil in accordance with ASTM D482-19.
[0123] In the catalytic depolymerization experiments, the catalyst is supported on a non-porous support with the help of a coating agent. Sand was used as a particulate non-porous support with a particle size distribution as summarized in Table 2, where 99% of the particles are smaller than 3 mm. Prior to use in the formation of the catalyst, the sand was pre-dried at 80 °C for 24 h in a drying oven with circulating air.
[0124] [Table 3]
[0125] Examples of the present disclosure:
[0126] A catalyst of the present disclosure using a mineral oil coating was prepared as follows.
[0127] 25.0 kg of sand was placed in a 60 L steel barrel with a screw cap and Teflon inlay. 350 mL of mineral oil was added (corresponding to 1.4 wt.% on sand). The drum was placed in a drum hoop mixer and rotated (approx. 100 rpm) for 1 h. 24.5 kg of the resulting mixture was placed in another drum and 500 g of the corresponding acidic component (corresponding to 2 wt.% loading) was added. The drum was placed in a drum hoop mixer and rotated (approx. 100 rpm) for 1 h. At the end of the mixing process, a well-flowing catalyst was obtained with particles of acidic component uniformly distributed on the surface of the sand particles.
[0128] The mineral oil used was Ondina X 432, available from Shell, and had the following characteristics:
[0129] [Table 4]
[0130] A catalyst of the present disclosure using a silica hydrogel coating was prepared as follows.
[0131] 25.0 kg of sand was placed in a 60 L steel barrel with a screw cap and Teflon inlay. 500 mL of water (corresponding to 2.0 wt.% relative to the sand) was added and the drum was placed in a drum hoop mixer and rotated (approximately 100 rpm) for 1 h. 24.5 kg of the resulting mixture was placed in another drum and 1000 g of a 1:1 milled free-flowing mixture of silica hydrogel and acidic compound (corresponding to a loading of 2 wt.%) was added. The drum was placed in a drum hoop mixer and rotated (approximately 100 rpm) for 1 h. At the end of the mixing process, a well-flowing catalyst was obtained with particles of acidic compound uniformly distributed on the surface of the sand particles. The resulting mixture was dried under vacuum at 120 °C for 6 h.
[0132] Silica hydrogel was prepared according to the procedure described in Example 1 of EP 1290042. The solids content of the hydrogel samples was 20 wt%. The D50 of the ground mixture of silica hydrogel and acidic components was 80-100 μm according to ASTM D4438.
[0133] Table 4 summarizes the catalysts used and the amounts of acidic compounds relative to the sand (unit: weight %).
[0134] [Table 5] Acidic compounds:
[0135] Zeolyst β (CP811E-75) is commercially available from PQ Corporation (Malvern, PA, USA).
[0136] Raw materials:
[0137] Some of the following organic waste materials were used as raw materials:
[0138] A: Pelletized agricultural and industrial packaging films.
[0139] A1) Shredded multi-layer PEX pipe waste with aluminum layer (grain size <20mm)
[0140] B) Shredded PEX pipe waste (grain size <20mm) containing EVOH
[0141] C) Shredded PEX pipe waste with an aluminum layer (grain size <20mm)
[0142] D) Shredded single layer PEX pipe waste (grain size <20mm)
[0143] E) Shredded high voltage cable bridge waste (grain size <20mm)
[0144] F) Shredded and pelletized mixed plastic waste from household packaging (comparison)
[0145] G) Pelletized agricultural and industrial packaging films
[0146] Feedstock properties averaged from the three sample analyses are summarized in Table 5.
[0147] [Table 6]
[0148] Ash: Ash content
[0149] TV: Total Volatile Matter
[0150] BD: Bulk density
[0151] Cl: Total chlorine content
[0152] PE: Polyethylene content
[0153] PP: Polypropylene content
[0154] PET: Polyethylene terephthalate content
[0155] PS: Polystyrene content
[0156] PA: Polyamide content
[0157] Other Content: Content of other impurities
[0158] The feedstock and catalyst were introduced into a reactor apparatus equipped with a heating unit, a gas discharge unit, a solid discharge unit, a condenser, and a screw for homogeneously mixing the reactor contents during depolymerization. The conditions of the depolymerization carried out are summarized in Table 6. The gaseous fraction obtained was further separated into liquid and gaseous depolymerization products by condensation. The amounts of the fractions obtained are also shown in Table 6.
[0159] [Table 7]
[0160] The above data show that the disclosed process is capable of producing a large amount of gaseous depolymerization products and maintaining good performance even when the feedstock is loaded with heterogeneous materials. The analytical results of the gaseous depolymerization products are summarized in Table 7.
[0161] [Table 8]
[0162] As can be seen from Table 7, the process of the present disclosure resulted in a gaseous depolymerization product containing a large amount of monomers useful as feedstock for polymerization after purification. Any gaseous saturated hydrocarbons can be treated in the usual manner and returned to the steam cracker oven.
[0163] Bulk density 60g / cm 3 Comparative experiments with polymer waste were also carried out with the same reactor setup. The experiments were repeatedly affected by plugging of the feed lines and fouling of the reactor, which made the experiments difficult.
Claims
1. 1. A process for the conversion of plastic waste to olefins, comprising: (i) depolymerizing a plastic waste feedstock containing more than 80% by weight of polyolefins based on a polymer fraction of said waste feedstock at a temperature ranging from 400 to 700°C in the presence of a catalyst, said polymer fraction of said waste feedstock containing non-polyolefin organic components in an amount of less than 7.0% by weight, preferably less than 6.0% by weight, more preferably less than 5.0% by weight, based on the total weight of the dry weight polymer fraction of said waste feedstock; (ii) recovering the gaseous fraction generated during pyrolysis; (iii) separating the recovered gaseous fraction to obtain a gaseous depolymerization product and a liquid depolymerization product, wherein the amount of the gaseous depolymerization product is greater than 60 wt.% based on total polyolefin content, but in the gaseous depolymerization product, the amount of C2-C4 olefins is 65 wt.% or more based on total amount of hydrocarbons.
2. 2. The process of claim 1, wherein the plastic scrap feedstock is characterized in that (a) it has a polyolefin content, in particular a total content of polypropylene (PP) and polyethylene (PE), of more than 85 wt.-%, based on the polymer content of the plastic scrap feedstock.
3. 3. The process according to claim 1 or 2, characterized in that the plastic waste feedstock has a bulk density of 70-500 g / L, preferably 100-450 g / L, if the polymer waste feedstock is present in shredded form, or a bulk density of 300-700 g / L, if the polymer waste feedstock is in pellet form, said bulk density being determined in accordance with DIN 53466, respectively.
4. 4. The process according to any one of claims 1 to 3, wherein in the polymer content of the plastic waste feedstock, the weight ratio PE / PP is ≧2.
5. 5. The process according to any one of claims 1 to 4, wherein the plastic waste feedstock is characterised in that (i) it has a total volatiles (TV) content of less than 4%, preferably less than 3%, measured as the weight loss of a 10 g sample after 2 hours at 100°C and 200 mbar.
6. 6. The process according to any one of claims 1 to 5, wherein the polymer content of the plastic waste feedstock is composed entirely of polyethylene (PE).
7. A process according to any one of claims 1 to 6, wherein the upper limit of the polyolefin content is 99 wt%, more preferably 98 wt%, especially 97 wt%, based on the total amount of plastic waste feedstock.
8. 8. The process of any one of claims 1 to 7, wherein the gas content in the depolymerized product is greater than 70 wt%.
9. 9. The process of claim 8, wherein the gas content in the depolymerized product is greater than 75 wt%.
10. In the gaseous depolymerization product, 2 ~C 4 The process of any one of claims 1 to 9, wherein the amount of olefins is at least 70 wt%, based on the total amount of hydrocarbons.
11. In the gaseous depolymerization product, 2 ~C 4 11. The process of claim 10, wherein the amount of olefins is 72 wt% or greater, based on the total amount of hydrocarbons.
12. In the gaseous depolymerization product, 2 ~C 4 The process according to any one of the preceding claims, wherein the amount of hydrocarbons is more than 80%, preferably more than 85%, based on the total amount of hydrocarbons.
13. 2. The process of claim 1, wherein the catalyst comprises as an active component an acidic compound deposited on a particulate non-porous support with the aid of a coating agent.
14. The acidic compound is an Al / Si mixed oxide, Al 2 O 3 14. The process of claim 13, wherein the silicate is selected from the group consisting of aluminosilicates, silica and zeolites.
15. 15. The process of claim 14, wherein the coating agent is selected from the group consisting of oil, inorganic hydrogel, or a combination thereof.
Citation Information
Patent Citations
Monomer recovery from polymer
JP1994500592A
Disposal system of plastic material
JP1999092589A
Method and apparatus for treating plastic waste
JP2002088375A
Conversion of plastics to monomers by acidic catalytic pyrolysis
US20220195140A1
Monomer recovery from polymeric materials
US5326919A